Implementing zero-trust architecture and quantifying the impact on system reliability and data protection in big data cloud infrastructures - Perumal, Arun Pandiyan; Ahire, Viralkumar (Edelweiss Applied Science and Technology, 2025)
The exponential growth of big data and the increasing complexity of cloud infrastructures have heightened the demand for robust security frameworks. This study presents the implementation process and analyzes the effect of zero-trust architecture (ZTA) on system reliability and data protection in big-data cloud environments. The methodology involves a comprehensive research approach, encompassing a review of existing research papers and the execution of a narrative review and content analysis to identify critical issues related to ZTA, system reliability, and data protection. The findings indicate that ZTA, with its robust access control mechanisms, can enhance data protection in a practical and tangible manner, thereby contributing to the enhancement of operational efficiency. This implies that organizations that embrace ZTA can fortify their data protection strategies and experience substantial real-world improvements in system reliability. A continuous monitoring system aids in the detection of anomalies and maintenance records, leading to reduced downtimes and improved system reliability. This study underscores the crucial role of strategic planning, resource management, and awareness training in the seamless integration of ZTA into organizational functionality for superior outcomes.